Cardiovascular risk factors in Moroccan women: systematic review and meta-analysis - Es-sabir Fatima; Lahlou Laila; Afaf Bouqoufi; Lahoucine Amsdar; Majdouline Obtel (BMC, 2024)
Abstract Background Cardiovascular diseases (CVD) are the major cause of disability and premature death. This is due to the ascending trend of consuming an unhealthy diet and obesity which increases the risk of hypertension and type 2 diabetes mellitus. The main aim of this review was to fill the knowledge gap by providing an up-to-date overview of the prevalence of CVD risk factors among women and to estimate the pooled prevalence among adolescent and pregnant women in Morocco. Methods The review included original cross-sectional studies reporting the prevalence of CVD risk factors in Moroccan women aged ≥ 15 years, published between January 2008 and December 2022. The databases searched included MEDLINE, Scopus, Web of Science, Google Scholar and national government publications (PROSPERO ID: CRD42023426809). Results Initially, 1471 articles were identified, and 76 studies were included. The most commonly reported CVD risk factor was obesity (reported in 56 studies), the prevalence of obesity varies according to the age groups of women with the rate being particularly high in urban women aged ≥ 35 years (ranging of 14-44.9%). Followed by diabetes (ranging from 7.2 to 12.6%) with a high rate in menopausal women. Hypertension prevalence ranged from 29.8 to 39.29%. Among adolescents, the overall prevalence of obesity was 3.15% (95% CI: 2.6%, 3.7%) and the prevalence of physical inactivity was 56.5% (95% CI: 36.9 − 76%). Among pregnant women, the overall prevalence of obesity was 26.8% (95% CI: 15.5 − 38.2%). Gestational diabetes and hypertension were 15.2% (95% CI: 6.3 − 24.1%) and 7.07% (95% CI: 2.5 − 11.6%), respectively. Conclusion This review highlights the significant burden of CVD risk factors among Moroccan women, with a high prevalences of diabetes, obesity, hypertension. The prevalences of these risk factors varies with age, being notably higher in older age groups. These findings underscore the need for targeted public health interventions to address these risk factors. Future research should focus on longitudinal studies and standardized assessment tools to enhance the robustness of prevalence estimates and inform effective prevention strategies.